OPTIMALISASI MODAL INTELEKTUAL DALAM MENINGKATKAN DAYA SAING PERGURUAN TINGGI DI ERA GLOBALISASI - Dalfa, Abu Bakar; Hesti Kusumaningrum; Rabiatul Adawiyyah (Cahaya Ilmu Bangsa Institute, 2024)
This research discusses important strategies for building intellectual capital in Indonesian educational institutions, detailing crucial steps such as professional recruitment, human resource development through mentoring and regular performance evaluations, and the creation of a positive working climate in schools. In addition, the study recognizes the key role of technology in improving accessibility and quality of learning, while scrutinizing potential risks such as over-reliance and access gaps. The conclusions provide deep insights into the strategies needed by educational institutions to face global competition, providing an essential basis for the development of education policies that are more effective and responsive to the changing dynamics in education.